2010
DOI: 10.1097/phm.0b013e3181a9ed9b
|View full text |Cite
|
Sign up to set email alerts
|

Is There Muscular Weakness in Parkinson's Disease?

Abstract: Controversy exists as to whether muscle weakness is present in Parkinson's disease (PD). Computerized literature searches identified clinical trials and reviews about muscular strength assessment in patients with Parkinson's disease, using the following databases: PubMed, Ovid MEDLINE, Ovid EMBASE, the Cochrane Database of Systematic Reviews, Cumulative Index to Nursing and Allied Health Literature, and Physiotherapy Evidence Database. Seventeen articles fulfilled all criteria for selection. These studies sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
2
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 22 publications
1
74
2
13
Order By: Relevance
“…Subsequent similar investigations testing the hypothesis of muscle weakness in PD have produced inconsistent results, 19 which may be related to differences in study design and, in light of the findings of the present study, limited statistical power. The differences found in the present cohort were highly significant but evident only for the upper extremities, and of great interest with respect to the initiation of the neurodegenerative processes of PD.…”
Section: Discussioncontrasting
confidence: 42%
“…Subsequent similar investigations testing the hypothesis of muscle weakness in PD have produced inconsistent results, 19 which may be related to differences in study design and, in light of the findings of the present study, limited statistical power. The differences found in the present cohort were highly significant but evident only for the upper extremities, and of great interest with respect to the initiation of the neurodegenerative processes of PD.…”
Section: Discussioncontrasting
confidence: 42%
“…Although the amount of references available is still restricted, there is a growing number of studies using this device to investigate the strength of different muscle groups in individuals with PD (2,5). In this study, the results of PT assessment in the isokinetic dynamometer showed a significant difference in quadriceps strength in individuals with PD, when compared to subjects without the disease matched for age and gender, corroborating previous studies (5,14).…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies, using sensitive equipment to assess muscle strength, have identified decreased strength in patients with PD when compared to control individuals, who are neurologically healthy (2,5,6). Furthermore, previous studies showed the relationship between muscle weakness and the decline in the basic and essential motor functions regarding the independence of these individuals, pointing out strength training as an important complementary approach (4, 7-10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations